2022
DOI: 10.1021/acsenergylett.2c00316
|View full text |Cite
|
Sign up to set email alerts
|

Synergistical Stabilization of Li Metal Anodes and LiCoO2 Cathodes in High-Voltage Li∥LiCoO2 Batteries by Potassium Selenocyanate (KSeCN) Additive

Abstract: Dramatic growth of lithium (Li) dendrite and structural deterioration of LiCoO2 (LCO) lead to rapid failure of a high-voltage Li∥LCO battery. The nitrile group (−CN) is beneficial to maintain the integrity of the LCO lattice due to its strong affiliation to Co ions, whereas the −CN bond is incompatible with the Li metal anode, leading to form a deleterious solid electrolyte interphase (SEI) film. Herein, a dual-functional electrolyte additive potassium selenocyanate (KSeCN) is introduced to construct stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Some other additives are designed with a higher intrinsic reduction potential compared with carbonate solvent molecules. However, they exhibit inferior affinity with Li + and thus cannot effectively migrate with Li + and be reduced under an electric field, which significantly decreases their effect. , Therefore, it is highly desirable to seek additives that are compatible with carbonate-based electrolytes and exhibit both high affinity with Li + and high reduction potential simultaneously so as to effectively regulate the interfacial chemistry.…”
mentioning
confidence: 99%
“…Some other additives are designed with a higher intrinsic reduction potential compared with carbonate solvent molecules. However, they exhibit inferior affinity with Li + and thus cannot effectively migrate with Li + and be reduced under an electric field, which significantly decreases their effect. , Therefore, it is highly desirable to seek additives that are compatible with carbonate-based electrolytes and exhibit both high affinity with Li + and high reduction potential simultaneously so as to effectively regulate the interfacial chemistry.…”
mentioning
confidence: 99%
“…Huang et al revealed that Mg-pillared LiCoO 2 , substituting the Octa-3a site in the Li slab by Mg 2+ , benefited to eliminate CEI overgrowth and enhance cycling stability within the voltage window of 3.0–4.6 V . Besides, the design of the functional electrolyte with appropriate additives is convenient and cost-effective, which holds great potential for commercial applications without a large-scale change of production conditions. , Electrolyte additives with specially designed functional groups could approach the inner Helmholtz layer and in situ participate in forming a uniform and stabilized CEI film on the surface of LCO, which blocks the reactions at the electrode/electrolyte interface. , For instance, Ruan et al adopted 5-acetylthiophene-2-carbonitrile (ATCN) to in situ construct a stable CEI film with low impedance, increasing the capacity retention of Li||LCO batteries from 53 to 91% after 200 cycles at a charge cutoff of 4.5 V . Anhydride-type additives have also been widely concerned and applied in LIBs, such as Li||LiNi 0.9 Co 0.05 Mn 0.05 O 2 and Li||LiNi 0.5 Mn 1.5 O 4 batteries (as summarized in Table S1), which however have rarely been well-investigated for LCO batteries at a high charge cutoff voltage of, e.g., 4.65 V until now.…”
Section: Introductionmentioning
confidence: 99%
“…By optimizing the electrolyte components, the property and stability of the electrode-electrolyte interface can be manipulated. In particular, designing electrolyte additives is considered one of the most economical, feasible, and scalable approaches to improve the electrochemical performance of batteries with the silicon-based anode. …”
Section: Introductionmentioning
confidence: 99%